Preliminary Phytochemical Screening and in vitro Antidiabetic Activity of Multi-Solvent Extracts of Marchantia paleacea (Asian Journal of Pharmaceutics (AJP), 2025)
Introduction: Increased blood sugar levels are a hallmark of diabetes mellitus, a metabolic disease caused by insulin resistance and decreased pancreatic insulin secretion. Marchantia paleacea, a species of liverwort, has demonstrated potential antidiabetic effects in both in vitro and in vivo studies. This study aims to conduct phytochemical screening and evaluate the in vitro antidiabetic activity of thallus extracts of M. paleacea using multiple solvents. Materials and Methods: Approximately 150 g of dried thallus powder was separately extracted using methanol, ethyl acetate, and chloroform through Soxhlet extraction. The resulting extracts underwent phytochemical analysis and were tested for in vitro antidiabetic activities, including α-amylase inhibition (AAI), α-glucosidase inhibition (AGI), and glucose uptake assay using 3T3-L1 adipocytes and L-6 myotubes. GraphPad Prism version 4 was employed to analyze the information, and one-way analysis of variance and Dunnett’s post-test were used. P-values below 0.05 were regarded as statistically significant. Results: All extracts contained flavonoids, phenolics, and terpenoids, which may be responsible for their antidiabetic effects, according to phytochemical screening. The strongest inhibitory action was shown by the methanol extract. With half-maximal inhibitory concentration values of 24.17 ± 0.002 μg/mL for AAI and 30.07 ± 0.016 μg/mL for AGI. In addition, the percentage of glucose uptake in 3T3-L1 and L-6 cell lines (449.72 ± 0.032 and 229.69 ± 0.20, respectively) was comparable to that of acarbose. Conclusion: The methanol extract was one of the examined extracts that demonstrated the strongest in vitro antidiabetic activity, likely because of the existence of bioactive phytoconstituents. These findings support the traditional medicinal use of M. paleacea for managing diabetes.